EMPOWERING GROWTH: UNVEILING ENTREPRENEURIAL TRAITS AND STRATEGIES AMONG AGRI ENTREPRENEURS IN BODOLAND TERRITORIAL REGION (BTR) OF ASSAM - Ramchiary, Chintumani; Singh, Amrit Pal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study attempts to examine the entrepreneurial traits possessed by the agricultural farmers of BTR and their strategies to survive and make their farm profitable. BTR is mainly agricultural region where the primary occupation is agriculture and is blessed with fertile land, favourable climate-weather conditions. The region is an autonomous region of Assam, India consisting of five districts i.e. Kokrajhar, Baksa, Chirang, Tamulpur and Udalguri. The study will give an insight regarding the entrepreneurial qualities possessed by the agricultural farmers and their strategies to be consistent in the farming and to make their farm profitable. The study is exploratory and analytical in nature and has interviewed 126 agricultural entrepreneurs from the Bodoland Territorial Region (BTR) of Assam purposively. Statiscal tools such as multiple response analysis, chi square test, mean, SD, frequencis and percentage have been used for analysing the data. The findings shows that entrepreneurial qualities such as hard work, consistency and experience in agriculture are the main attributes perceived to be possessed by the agri entrepreneurs. Whereas, the strategies such as adopting modern method of farming, proper planning, connection with departmental officials, farm diversification, mixed and multiple cropping are some of the major strategies adopted by the agri entrepreneurs of BTR, Assam.The findings provide valuable insights for policymakers to design targeted policies; by identifying effective strategies used by successful agri-entrepreneurs, the research offers a roadmap for aspiring entrepreneurs and foster growth. This can stimulate rural entrepreneurship, economic empowerment, reduce migration and promote self-sufficiency within the BTR region of Assam.